Analysis of student’s critical thinking skills and creativity after problem-based learning with STEM integration - Dissa Feby Octafianellis; Sudarmin Sudarmin; Nanik Wijayanti; Helina Panca (Journal of Science Education Research, 2021)
Problem based learning (PBL) is one of the ideal learning models to meet the goals of 21st century education. It involves the 4C principles of critical thinking, communication, collaboration, and creativity. This study aims to analyze students’ critical and creative thinking skills after the use of STEM integrated PBL. This type of study is a mix method research with sequential explanatory design. The research subjects are 100 students of class XI IPA Christian Tri Tunggal Senior High School. The research instruments were written test questions, observation, interviews, and documentation. The results of the validation of the instruments by experts show a Cronbach Alpha score of 0.79. The data analysis is conducted through quantitative descriptive accompanied by t-test and N-gain test. The results of the analysis show that students’ critical thinking skills achieve a good criteria with the highest achievement in the aspect of providing simple explanations. Students’ creative thinking skills achieve a good criteria with the highest achievement on the flexibility aspect, namely providing various interpretations of a discourse, story, or problem. Hence, STEM integrated PBL can develop students’ critical and creative thinking skills